Managing Water and Agroecosystems for Food Security - Boelee, Eline (CABI, 2014)
There is broad consensus on the need to improve water management and to invest in water for food, as these are critical to meeting the Millennium Development Goals (MDGs). The role of water in food and livelihood security is a major issue of concern in the context of persistent poverty and continued environmental degradation. Although there is considerable knowledge on the issue of water management, an overarching picture on the water–food– livelihoods–environment nexus is missing, leaving uncertainties about management and investment decisions that will meet both food and environmental security objectives. The Comprehensive Assessment (CA) of Water Management in Agriculture is an innovative multi-institute process aimed at identifying existing knowledge and stimulating thought on ways to manage water resources to continue meeting the needs of both humans and ecosystems. The CA critically evaluates the beneﬁ ts, costs and impacts of the past 50 years of water development and the chal- lenges to water management currently facing com munities. It assesses innovative solutions and explores the consequences of potential invest ment and management decisions. The CA is designed as a learning process, engaging networks of stakeholders to produce knowledge synthesis and methodologies. The main output of the CA is an assessment report that aims to guide investment and management decisions in the near future, considering their impact over the next 50 years in order to enhance food and environmental security to support the achievement of the MDGs. This report was published in 2007 under the title Water for Food, Water for Life: A Comprehensive Assessment of Water Management in Agriculture, but CA research and knowledge- sharing activities have continued to expand the assessment.